Effect of Different Doses of Oral Cholecalciferol on Serum 1,25(OH)2D in Vitamin D Deficient Schoolchildren - Ghazi, A. A.; Hosseinpanah, F.; Abdi, H.; Hedayati, M.; Hasheminia, M.; Ghazi, S.; Azizi, F. (Hormone and Metabolic Research, 2016)
Data regarding 1,25-dihydroxycholecalciferol in adolescents are limited. We aimed to determine serum levels of this active metabolite of vitamin D and the effects of different doses of vitamin D on its concentration in schoolchildren with high prevalence of vitamin D deficiency. In a previously published randomized double-blind, placebo-controlled trial, 210 subjects, aged 14–20 years, were assigned to 3 regimens of vitamin D treatment: group A (n=70) received 50 000 U oral cholecalciferol monthly, group B (n=70), 50 000 U bimonthly, and group C (n=70), placebo. Serum 25(OH)D, calcium, parathyroid hormone, and bone markers were measured at baseline and after 2 and 5 months of treatment. In the present study, serum levels of 1,25(OH)2D were measured in 97 boys and 95 girls. At baseline, girls had significantly higher concentrations of 1,25(OH)2D than boys (36, IQR: 24, 63 vs. 30, IQR: 15, 57.5 pmol/l; p<0.01). There was no significant correlation between serum levels of 25(OH)D and 1,25(OH)2D in the total population (Spearman rho=− 0.111; p=0.126), boys (Spearman rho=0.008; p=0.941), and girls (Spearman rho=0.036; p=0.729). Also, 1,25(OH)2D values did not change over time in different study groups. Moreover, total and sex-stratified analysis did not show any significant difference between different groups at different times of the study period. In an adolescent population with high prevalence of hypovitaminosis D especially in girls, 1,25(OH)2D values were higher in girls than boys. There was no significant change in 1,25(OH)2D concentrations with different doses of vitamin D.
Keywords: hypovitaminosis D; 1,25-dihydroxycholecalciferol; adolescents